"1979 : year of economic turnaround - Fraser" - Pryor, Geoff, 1944- (1979)
Canberra singled out for special budget treatment.
Published in the Canberra Times on 23 February 1979.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Fraser, Malcolm, -- 1930-2015 -- Caricatures and cartoons; Australia -- Economic conditions -- 1976-1990 -- Caricatures and cartoons